Susan Richardson interviewed by Nikki Henningham in the Academy of the Social Sciences in Australia collection - Richardson, Sue, 1946-; Henningham, Nicola, 1960- (2007)
Susan Richardson gives a summary of her career highlights; early biographical details, siblings, schooling. She then speaks about her motivation to become an economist; enrolling at the University of Melbourne in Bachelor of Commerce; refers to article 'Why women make lousy economists'; feminism and feminist scholarship; her fields of research; academic life; her first publication; her early work at La Trobe University after completion of undergraduate work at University of Melbourne; her decision to undertake a PhD; topic of thesis; moving University of Adelaide for first academic appointment before PhD completed; research interests after moving to Adelaide; working with sociologist to write 'Living Decently' a book dealing with the problem of poverty; relationship of 'Living Decently' to the Henderson Enquiry into Poverty.
Richardson discusses her thoughts on the relationship between scholarship, universities and governments; her involvement with the Productivity (then Industry) Commission; work on other Government Advisory Boards and Instrumentalities; combining work and family and motherhood; Fiona Stanley and Margot Prior; Labour Market research and it's impact on children's lives; the importance of the Academy of the Social Sciences (ASSA) personally and professionally; women on Boards; her Board Involvement; gender and the discipline of economics; employment at the National Institute for Labour Studies and the type of work undertaken; the Australian labour market; ASSA funding and review process; opportunities for non-academic social scientists in the ASSA; strengths and Advocacy Role of the ASSA; office bearers and staff; proportions of women in the academy; comments on some ASSA projects; collaboration between ASSA and Australian Bureau of Statistics, social science analysis of the census; other targets for interview; other influences, personal and intellectual.
Recorded on February 27, 2007 at Melbourne, Vic.
Digital master available
Mode of access: Internet via World Wide Web.
Timed summary (7 p.) and uncorrected transcript (typescript, 94 leaves).
Keywords: Richardson, Sue, -- 1946- -- Interviews; Travers, Peter; Academy of the Social Sciences in Australia; Economists -- Australia -- Interviews; Economics -- Australia; Economists; Academics